O discurso político de parlamentares maranhenses no twitter: uma análise das formações discursivas - SILVA, Anaildo Pereira da (2021)
In this work, we investigate the discourse of Maranhão politicians on Twitter. We consider that social media are spaces for the production and dissemination of discourse. Thus, there is a concern about how the political discourse of Maranhão is constituted in digital social media. Thus, considering the engagement of these agents in digital social media, we ask ourselves: how do the linguistic markers present in publications on the social network digital Twitter reflect the discursive formation of the Maranhão politician? To respond to this concern, we set as general objective to analyze the discursive representation of linguistic resources used in the constitution of the regional political discourse published on Twitter. Specifically, we are willing to: identify the linguistic markers present in the texts published on Twitter; verify the meanings reflected by the way of using linguistic elements; analyze the discursive regularities that constitute the Maranhão political discourse. As a basic theoretical contribution of this research, we use the studies of Charaudeau (2013), to explain how social media can be used to make political discourse and the power they provide to these discourses, and Charaudeau (2018), to reflect on the political discourse and the strategies used by politicians to consolidate their discourse; Pêcheux ([1975]2014a, [1969]2014b, [1983]2014c) to work on the concept of discursive and ideological formation that allows us to understand the senses according to the positions assumed by the subjects, and to work on the imaginary formations involved in the discursive process, respectively. Adding to the theoretical efforts cited, we seek the understanding of Maingueneau (1997, [2014]2015) about interdiscourse and the types of discourses present in the publications of Maranhão parliamentarians. We also align Foucault ([1969]2008), regard to the study of discursive regularities, a concept that we consider relevant to this study since we seek to understand how Maranhão political discourse is constituted in digital social media. We listed the studies of Koch (2003, 2018, 2020), Authier-Revuz (2004), and Benveniste (1991) regard to the analysis of linguistic resources present in the construction of texts [twittes] of Maranhão parliamentarians. The corpus used in this research consists of 114 (one hundred and fourteen) publications (tweets)of 06 (six) Maranhão parliamentarians on Twitter in the period between 2019 and 2021. As a methodological procedure, we consider the following steps: 1) the qualitative method that allows us to analyze categories of discourse, positions-subject, etc. and treat the corpus subjectively; 2) the indicia paradigm of Ginzburg (1996), that allows the perception of clues and traits that a priori is not perceived, and 3) the discursive method to analyze the constitutive elements of discursive production allowing us to go beyond the textual surface, that is, capable of leading us to the constitutive elements of the discursive production of Maranhão parliamentarians. At the end of this research, it was concluded that the use of linguistic resources is regularly done to meet discursive purposes in the publications made by Maranhão parliamentarians in given production conditions, thus when walking the proposed path, a regular discourse was reached, the legal discourse, and, therefore, this is the Maranhão parliamentary discourse on Twitter.